Information asymmetry and industry 4.0 among small and medium enterprise (SME) in Malaysian halal industry - Ng, Suat Thing; Mohd Hasimi Yaacob; Norazlan Alias (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study attempts to investigate the participant(s) halal industry information asymmetry issues and their intention, if any, to mitigate it. Additionally, this study also investigates the moderating effects of their perceptions towards industry 4.0 adoption and their intentions of using industry 4.0 to mitigate information asymmetry. This research is exploratory research. We adapted the questionnaire based on “Agency Theory and the Technology Acceptance Model” by combining management and technology literature into single-sourced literature. The research using the SmartPLS software “Partial Least Squares (PLS)” modelling and the 2-step approach to test the model development. The concepts of private information, hidden information, and the lack of perfect information have facilitated these companies’ top management intentions to mitigate these information asymmetry issues. The results also show that the top management of halal industry has the intention to reduce information asymmetry through industry 4.0 adoption as they perceived industry 4.0 is useful, easy to use, is cost affordable, and provides a high system and content quality.